POTRET KEMASAN MINUMAN JANJI JIWA SEBAGAI MEDIA PENCITRAAN DI SOSIAL MEDIA INSTAGRAM - Renzy Ayu Rohmatillah (Universitas Lancang Kuning, 2023)
This research mainly discussed the phenomenon of photo-sharing on Instagram with different aims. One of them was to show a person's identity or a particular group. This study specifically examined a beverage brand growing rapidly on Instagram named